Rehabilitation of Concussion and Persistent Postconcussive Symptoms - Wilber, Charles G.; Leddy, John J.; Bezherano, Itai; Bromley, Lacey; Edwards, Amanda E.; Willer, Barry S.; Haider, Mohammad N. (Seminars in Neurology, 2021)
Concussion and persistent postconcussive symptoms (PPCS) are encountered by clinicians in sports medicine, pediatrics, neurology, physiatry, emergency medicine, and primary care. Clinical management may require a multidisciplinary approach. This article presents a structured method for the diagnosis of concussion and PPCS in the outpatient setting, which includes a history, physical examination, and additional tests as clinically indicated to help identify underlying symptom generators. Treatment for concussion and PPCS should be individualized, based on predominant signs and symptoms, and can include subsymptom threshold aerobic exercise, cervical physical therapy, vestibulo-ocular rehabilitation, behavioral and cognitive psychotherapy, and some symptom-specific pharmacological therapies.
Keywords: concussion; persistent post concussion symptoms; post-concussion syndrome; cervicogenic headache; active rehabilitation